Preliminary Analysis of Bilberry NaDES Extracts as Versatile Active Ingredients of Natural Dermocosmetic Products: In Vitro Evaluation of Anti-Tyrosinase, Anti-Hyaluronidase, Anti-Collagenase, and UV Protective Properties - Milica Martinović; Ivana Nešić; Ana Žugić; Vanja M. Tadić (Plants)
Bilberry (Vaccinium myrtillus L.) fruits represent the recognized wellspring of bioactive compounds with various documented bioactivities. Although bilberry leaves are often treated as industrial by-products, they also represent a valuable source of phytochemicals with potential dermocosmetic applications. In this study, extracts of bilberry fruits and leaves were prepared using both conventional solvents (water and 50% ethanol) and natural deep eutectic solvents (NaDES) as green, biodegradable alternatives. The aim of this study was to examine the UV protective activity and inhibitory potential of those extracts against some enzymes (tyrosinase, hyaluronidase, collagenase) that are important in terms of skin conditioning and skin aging. The results of in vitro tests have shown the superiority of NaDES extracts compared to conventional extracts regarding all tested bioactivities. In addition, bilberry leaves extracts were more potent compared to fruit extracts in all cases. The most potent extract was bilberry leaf extract made with malic acid–glycerol, which exhibited strong anti-tyrosinase (IC50 = 3.52 ± 0.26 mg/mL), anti-hyaluronidase (IC50 = 3.23 ± 0.30 mg/mL), and anti-collagenase (IC50 = 1.84 ± 0.50 mg/mL) activities. The correlation analysis revealed correlation between UV protective and anti-tyrosinase, UV protective and anti-collagenase as well as between anti-hyaluronidase and anti-collagenase activity. UV protection and anti-tyrosinase activity correlated significantly with chlorogenic acid and hyperoside contents in extracts. The extracts with the best activities also demonstrated a good safety profile in a 24 h in vivo study on human volunteers.